A unified modeling method for dynamic analysis of GPLs-FGP sandwich shallow shell embedded SMA wires with general boundary conditions under hygrothermal loading. (1st January 2022) - Zhao, Jing; Hu, Jinzhai; Wang, Tianhao; Li, Hui; Guan, Jialin; Liu, Jincan; Gao, Zhijiang
Highlights: A novel class of sandwich shallow shell reinforced by the GPLs-FGP is proposed. The structural thermal stability is improved by embedding the SMA wires. The dynamic behaviors of the sandwich shallow shell are analyzed by using the Jacobi-Ritz method. The hygrothermal loading model is constructed by using the energy method. Abstract: In this research, the dynamic analysis of graphene platelets (GPLs) reinforced functionally graded porous (FGP) sandwich shallow shell embedded shape memory alloy (SMA) wires with general boundary conditions under hygrothermal loading is conducted. Four different porosity distributions of FGP reinforced with four various GPLs dispersion patterns are considered. Based on the Brinson formulation, the constitutive equation of the SMA is established. The energy functional of the sandwich shallow shell is constructed by employing the Hooke's law and the first-order shear deformation theory (FSDT). Ultimately, the dynamic characteristics of the sandwich shallow shell are obtained by solving the energy functional with the Rayleigh-Ritz method. After the verification of accuracy and reliability, parametric studies on the effects of material properties, geometrical parameters, and boundary conditions are investigated.